FENOMENA CERITA ALTERNATIVE UNIVERSE (AU) BERTEMA HOMOSEKSUAL DI MEDIA SOSIAL TWITTER (STUDI ETNOGRAFI VIRTUAL PADA AKUN BASE @aubxbfess) - Febriyanti, Andini; Ekomila, Sulian (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: This research discusses the phenomenon of Alternative Universe (AU) type fanfiction with a homosexual theme of the BxB type found on the @aubxbfess base on Twitter social media. This research focuses on knowing why followers like AU BxB and the motivation of followers to become authors. The research method used is qualitative research with a virtual ethnographic approach. Data collection techniques through participant observation, interviews, and documentation. The data analysis technique used is the Analysis of Cyber Media (AMS). Based on the study's results, it was found that the base @aubxbfess, since 2020, has become a forum for readers and authors to promote and search for AU BxB, specifically boy groups NCT and WayV. The reason followers like AU BxB is due to jealousy of their favorite idol if paired with a girl, and other reasons assume that AU BxB has a more varied story. The motivation for base followers to like AU BxB is that they like same-sex idol interactions because they want to channel their writing talents and relieve stress. Based on Cyber ​​Media Analysis at the media space level, the author's position is as a participant who participates in reading, giving likes, retweeting and providing comments on AUs that are shared on the base, apart from that the author also observes and explains the procedures for creating an account and sending comments on the base. At the document level, the media looks at cultural artifacts on the base @aubxbfess which are characterized by the presence of terms that can only be understood by the base's followersAt the media object level, it sees the interaction of followers, and at the experience level, it connects real-world relationships with life in cyberspace. Keywords: Twitter, Base, Alternative Universe, Homosexual